2016
DOI: 10.3762/bjoc.12.217
|View full text |Cite
|
Sign up to set email alerts
|

TBHP-mediated highly efficient dehydrogenative cross-oxidative coupling of methylarenes with acetanilides

Abstract: A TBHP-mediated dehydrogenative cross-oxidative-coupling approach has been developed for the synthesis of N-arylbenzamides from methylarenes and acetanilides. This cross-coupling method is free of transition metal catalysts and ligands, and no extra organic solvents are required, which make it an useful and attractive strategy for the straightforward construction of C–N bonds. Besides, this conversion is an important complement to the conventional C–N forming strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…After identifying the best reaction conditions, the substrate scope of this transformation was investigated. As summarized in Scheme , a variety of aryl iodides and diverse aryl acetamides carrynig both electron‐donating and electron‐withdrawing substituents have been tolerated this procedure to give the corresponding products up to 92% yield under the selected conditions (Scheme , 3h) . Not only aryl acetamides but also heteroaryl acetamides are suitable substrates for this transformation (Scheme , 3m).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After identifying the best reaction conditions, the substrate scope of this transformation was investigated. As summarized in Scheme , a variety of aryl iodides and diverse aryl acetamides carrynig both electron‐donating and electron‐withdrawing substituents have been tolerated this procedure to give the corresponding products up to 92% yield under the selected conditions (Scheme , 3h) . Not only aryl acetamides but also heteroaryl acetamides are suitable substrates for this transformation (Scheme , 3m).…”
Section: Resultsmentioning
confidence: 99%
“…In continue, acylation of acetamide and deacylation of the formed product (III) via hydrolysis, yields the corresponding product. The selective hydrolysis of COCH 3 over COPh may be referred to their relative stabilities 17b…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Слід зазначити, що така інтерпретація є доволі спрощеною з тієї точки зору, що зовсім не враховує особливостей тонкого розщеплення сигналів ароматичних фрагментів, які в експериментальних спектрах ЯМР зазвичай представлені в якості нероздільних мультиплетів в області 7,2-7,9 м.д. 23,24 .…”
Section: рис 5 характеристичні сигнали у пмр-спектрі бензаніліду (1)unclassified
“…In 2016, Chen et al. reported oxidative cross‐coupling approach for the synthesis of N ‐arylbenzamides from methylarenes and acetanilides employing I 2 as a catalyst and TBHP as an oxidant (Scheme ) . The authors found that molecular iodine was essential for this reaction to proceed.…”
Section: Synthesis Of Amides From Methylarenesmentioning
confidence: 99%